2021
DOI: 10.1016/j.annepidem.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality in California based on death certificates: disproportionate impacts across racial/ethnic groups and nativity

Abstract: Purpose To examine characteristics of coronavirus disease 2019 (COVID-19) decedents in California (CA) and evaluate for disproportionate mortality across race/ethnicity and ethnicity/nativity. Methods COVID-19 deaths were identified from death certificates. Age-adjusted mortality rate ratios (MRR) were compared across race/ethnicity. Proportionate mortality rates (PMR) were compared across race/ethnicity and by ethnicity/nativity. Results We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Foreign-born individuals also had elevated proportionate mortality rates compared with individuals born in the United States, in an examination of death files in California. 11 Similar findings have been reported in other countries, including the United Kingdom and Canada. 12 , 13 Together with our results, these studies highlight the disproportionate burden of the SARS-CoV-2 pandemic for immigrant families and families who prefer a language other than English, and support continued calls for large-scale interventions to reverse systemic inequities for those families.…”
Section: Discussionsupporting
confidence: 83%
“…Foreign-born individuals also had elevated proportionate mortality rates compared with individuals born in the United States, in an examination of death files in California. 11 Similar findings have been reported in other countries, including the United Kingdom and Canada. 12 , 13 Together with our results, these studies highlight the disproportionate burden of the SARS-CoV-2 pandemic for immigrant families and families who prefer a language other than English, and support continued calls for large-scale interventions to reverse systemic inequities for those families.…”
Section: Discussionsupporting
confidence: 83%
“…We focus our modeling framework on the risk factors age, comorbidities, obesity, and smoking status as these demographic and medical conditions have consistently been identified across various studies as factors inducing the probability of progressing to severe illness given COVID-19 infection [ 8 ]. We do not include race/ethnicity as a factor, because although strongly predictive of the risk of overall mortality from COVID-19 [ 17 ], it has been shown that increased exposure risk and not race per se explains racial disparities in COVID-19 health outcomes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extreme disparities in infection incidence and mortality have been observed for different communities within LAC. This includes incidence rates up to 15 times higher in low-income neighborhoods in East LA with high percentages of essential workers than in affluent communities in West LA [ 14 ], and COVID deaths as a proportion of the typical total deaths 11.6 times higher for young, foreign-born Latinx than for young, U.S.-born, non-Hispanics (for California) [ 17 ]. These large differences in infection incidence and death will undoubtedly translate into large differences in probabilities of disease progression and IFR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of our COVID-19 mortality assessment method have been previously published ( Garcia et al, 2021 ). Briefly, we used an internally developed algorithm to identify COVID-19-related deaths using the new International Statistical Classification of Diseases and Related Health Problems code for COVID-19 (U07.1) and a keyword search of variables related to immediate and underlying causes of death or other significant conditions that contributed to death.…”
Section: Methodsmentioning
confidence: 99%